ARTYKUŁ PRZEGLĄDOWY/REVIEW PAPERAntineutrophil cytoplasmic antibodies (ANCA) - Puszczewicz, Mariusz (Reumatologia/Rheumatology, 2005)
The immunological characteristics and method of ANCA testing were presented in the paper. Author shows connection between ANCA and vasculitis, especially with Wegener`s granulomatosis, and clinical significance of ANCA as well as their role in the pathogenesis of vasculitis.